Vitamin B12 and folate deficiency in chronic heart failure. Issue 4 (16th October 2014) - van der Wal, Haye H; Comin-Colet, Josep; Klip, Ijsbrand T; Enjuanes, Cristina; Beverborg, Niels Grote; Voors, Adriaan A; Banasiak, Waldemar; van Veldhuisen, Dirk J; Bruguera, Jordi; Ponikowski, Piotr; Jankowska, Ewa A; van der Meer, Peter
Abstract : Objective: To determine the prevalence, clinical correlates and the effects on outcome of vitamin B12 and folic acid levels in patients with chronic heart failure (HF). Methods: We studied an international pooled cohort comprising 610 patients with chronic HF. The main outcome measure was all-cause mortality. Results: Mean age of the patients was 68±12 years and median serum N-terminal prohormone brain natriuretic peptide level was 1801 pg/mL (IQR 705–4335). Thirteen per cent of the patients had an LVEF >45%. Vitamin B12 deficiency (serum level <200 pg/mL), folate deficiency (serum level <4.0 ng/mL) and iron deficiency (serum ferritin level <100 µg/L, or 100–299 µg/L with a transferrin saturation <20%) were present in 5%, 4% and 58% of the patients, respectively. No significant correlation between mean corpuscular volume and vitamin B12, folic acid or ferritin levels was observed. Lower folate levels were associated with an impaired health-related quality of life (p=0.029). During a median follow-up of 2.10 years (1.31–3.60 years), 254 subjects died. In multivariable proportional hazard models, vitamin B12 and folic acid levels were not associated with prognosis. Conclusions: Vitamin B12 and folate deficiency are relatively rare in patients with chronic HF. Since no significant association was observed between mean corpuscular volume and neither vitamin B12 nor folic acid levels, this cellular index should be used with caution in the differential diagnosis of anaemia in patients with chronic HF. In contrast to iron deficiency, vitamin B12 and folic acid levels were not related to prognosis.